Relics in medieval altarpieces? Combining X-ray tomographic, laminographic and phase-contrast imaging to visualize thin organic objects in paintings - Krug, Kris; Porra, Liisa; Coan, Paola; Wallert, Arie; Dik, Joris; Coerdt, Andrea; Bravin, Alberto; Elyyan, Muthaffar; Reischig, Péter; Helfen, Lukas; Baumbach, Tilo (Journal of synchrotron radiation, 2008)
X‐ray radiography is a common tool in the study of old master paintings. Transmission imaging can visualize hidden paint layers as well as the structure of the panel or canvas. In some medieval altarpieces, relics seem to have been imbedded in the wooden carrier of paintings. These are most probably thin organic fibrous materials such as paper or textile, which in traditional radiography are shadowed by the more absorbing surrounding material. This paper studies the application potential of synchrotron‐based tomographic and laminographic imaging complemented with phase‐contrast imaging for detection of such relics. The techniques are applied to a dummy painting. The results demonstrate that by using these imaging methods it is possible to three‐dimensionally visualize hidden cavities in panels and detect thin fibrous low‐Z materials sandwiched between a high‐Z paint layer and a thick wooden panel.